The Carotid Sinus Nerve—Structure, Function, and Clinical Implications. Issue 4 (2nd May 2018) - Porzionato, Andrea; Macchi, Veronica; Stecco, Carla; De Caro, Raffaele
ABSTRACT: Interest has been renewed in the anatomy and physiology of the carotid sinus nerve (CSN) and its targets (carotid sinus and carotid body, CB), due to recent proposals of surgical procedures for a series of common pathologies, such as carotid sinus syndrome, hypertension, heart failure, and insulin resistance. The CSN originates from the glossopharyngeal nerve soon after its appearance from the jugular foramen. It shows frequent communications with the sympathetic trunk (usually at the level of the superior cervical ganglion) and the vagal nerve (main trunk, pharyngeal branches, or superior laryngeal nerve). It courses on the anterior aspect of the internal carotid artery to reach the carotid sinus, CB, and/or intercarotid plexus. In the carotid sinus, type I (dynamic) carotid baroreceptors have larger myelinated A‐fibers; type II (tonic) baroreceptors show smaller A‐ and unmyelinated C‐fibers. In the CB, afferent fibers are mainly stimulated by acetylcholine and ATP, released by type I cells. The neurons are located in the petrosal ganglion, and centripetal fibers project on to the solitary tract nucleus: chemosensory inputs to the commissural subnucleus, and baroreceptor inputs to the commissural, medial, dorsomedial, and dorsolateral subnuclei. The baroreceptor component of the CSN elicits sympatho‐inhibition and the chemoreceptor component stimulates sympatho‐activation. Thus, in refractory hypertension and heart failure (characterized by increased sympathetic activity), baroreceptor electrical stimulation, and CB removal have been proposed. Instead, denervation of the carotid sinus has been proposed for the "carotid sinus syndrome." Anat Rec, 302:575–587, 2019. © 2018 Wiley Periodicals, Inc.